Outsourcing as a customer satisfaction mechanism: The case of a hemodialysis company in Arequipa - Carcasi Laura, Edgar Alfredo (2020)
We sought to compare the satisfaction of patients on hemodialysis, in the outsourced service of a company and the Arequipa social security, in the year 2017. Study with a quantitative approach, retrospective and comparative cross-sectional observational design. The sample it made up of 148 and 109 patients from the company Sermedial SAC and EsSalud. The instrument prepared based on the SERVPERF model by Cronin and Taylor for both entities. The results the patients satisfied were: in tangible elements the company Sermedial 68.24% and EsSalud 63.30%. In reliability, the company Sermedial 59.46% and EsSalud 54.13% also showed a level of satisfaction. In response capacity, the company Sermedial 65.54% and EsSalud 25.69% of its clients satisfied. In empathy, the company Sermedial 58.11% and EsSalud 55.05% of its customers satisfied. And in security, the company Sermedial obtained 85.81% and EsSalud 66.06% of its clients satisfied. The most valued level of satisfaction comes from the Sermedial company about EsSalud. Conclusion: There are significant differences in the level of customer satisfaction on hemodialysis, in both services with a p value <0.5. Significant differences it found in both entities, but the company Sermedial SAC, exceeds the favorable averages in all the dimensions evaluated, about EsSalud, with a p value of <0.05.